Seed-Mediated Synthesis of Gold Nanorods at Low Concentrations of CTAB - Wei, Ming-Zhang (ACS Omega, 2021)
[Image: see text] Although gold nanorods capped with hexadecyltrimethylammonium bromide (CTAB) have been prepared through the seed-mediated method for their use in diagnostics and therapeutics, the toxicity of AuNRs@CTAB limits their practical applications in the biomedical field. In this work, the synthesis and tuning of gold nanorods at very low concentrations of CTAB (as low as 0.008 M) was successfully achieved by using the seed-mediated method. Furthermore, we managed to optimize the growth conditions by changing the amount of seeds, AgNO(3), and/or HCl. At low CTAB concentrations, gold nanorods with tunable size and aspect ratio, high monodispersity, and high purity were obtained and studied by UV–vis spectroscopy, transmission electron microscopy, and Mie–Gans theoretical calculations. This work revealed a method of nanoparticle growth that may be extended to synthesize other nanomaterials such as Ag, Cu, Pd, and Pt at such low CTAB concentrations.